Pengaruh Pengangguran Dan Ketimpangan Gender Terhadap Kemiskinan Di Jawa Timur - Rozul, Risky Nada; Priyono, Achmad Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to determine the effect of unemployment and gender inequality on poverty partially and simultaneously. The type of research used is secondary data in the form of a time series with a quantitative approach. This research was conducted in districts and cities in the East Java Province. The population in this research is poverty in the people of East Java Province. The sample is part of the population which will later be used as research material in this research on the number of poor people in East Java Province in 2020-2023. The research results show that there is a significant influence between the variables Unemployment (X1) and Gender Inequality (X2) on Poverty (Y) in East Java. The Unemployment variable (X1) does not have a significant effect on poverty. The Gender Inequality variable (X2) has a significant effect on poverty. Keywords: Unemployment, Gender Inequality, and Poverty